2020
DOI: 10.1097/md.0000000000019583
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of photobiomodulation in salivary production of patients with xerostomy induced by anti-hypertensive drugs

Abstract: Introduction: Hypertension (systemic arterial hypertension [SAH]) is a systemic condition that affects about 30% of the world population, according to data from the World Health Organization (WHO). Drugs used to control this disease have the potential to induce xerostomia, an oral condition in which the decrease of the salivary flow is observed and whose presence leads to the increase of the index of caries, periodontal disease, loss of the teeth, dysgeusia, difficulty of mastication, dysphagia, bad breath and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…In this respect, extraoral irradiation over the gland itself is considered to be more effective than exclusively intraoral administration [ 14 ]. In previous biostimulation studies of the sublingual glands, a wavelength of 660 nm was the most widely used setting, though a number of authors used longer wavelengths, particularly for the biostimulation of glands at the extraoral level (780–904 nm) [ 14 , 29 , 30 ]. We used the same wavelength as Campos-Louzeiro et al in their study published in 2020 (810 nm) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, extraoral irradiation over the gland itself is considered to be more effective than exclusively intraoral administration [ 14 ]. In previous biostimulation studies of the sublingual glands, a wavelength of 660 nm was the most widely used setting, though a number of authors used longer wavelengths, particularly for the biostimulation of glands at the extraoral level (780–904 nm) [ 14 , 29 , 30 ]. We used the same wavelength as Campos-Louzeiro et al in their study published in 2020 (810 nm) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…It would be very useful to stratify xerostomia according to its underlying cause when assessing the efficacy of PBM. Relatedly, in elderly patients with xerostomia due to the use of antihypertensive drugs, Zarvos-Varellis et al [ 30 ] found photodynamic therapy to be effective in reducing xerostomia. In turn, Vidovic-Juras et al, in their study in 2010 [ 37 ], found the Xerostomia VAS score to improve as a result of laser treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The salivary flow rate and its pH were influenced by hypertension and the salivary flow rate was lower in borderline hypertension people than in normotensives [ 32 , 33 ]. According to previous study, drugs utilized for controlling hypertension also have a potential to induce xerostomia [ 34 , 35 ]. Drugs controlling hypertension act on central alpha 2 adrenergic receptors, and the activation of alpha 2 adrenoceptor is in the lateral hypothalamus which is an important central area for the control of salivary secretion and resulting in xerostomia [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our search strategy did not identify papers on the impact of PBM in patients with medication-induced hyposalivation, despite its higher prevalence (Millsop et al, 2017;Ship et al, 2002). A study protocol has been published recently to evaluate the effect of PBM in patients with antihypertensive drug-induced xerostomia (Varellis et al, 2020) so that may endorse the need for further studies that deal with this population. Our review also did not retrieve studies on patients who had undergone radiotherapy, despite the recognized glandular changes associated with the irradiation (Avila et al, 2009) that involved xerostomia/hyposalivation, both dose-dependent.…”
Section: Discussionmentioning
confidence: 99%